Development of a real-time internal and external marker tracking system for particle therapy: a phantom study using patient tumor trajectory data. (15th February 2017) - Cho, Junsang; Cheon, Wonjoong; Ahn, Sanghee; Jung, Hyunuk; Sheen, Heesoon; Park, Hee Chul; Han, Youngyih
Abstract: Target motion–induced uncertainty in particle therapy is more complicated than that in X-ray therapy, requiring more accurate motion management. Therefore, a hybrid motion-tracking system that can track internal tumor motion and as well as an external surrogate of tumor motion was developed. Recently, many correlation tests between internal and external markers in X-ray therapy have been developed; however, the accuracy of such internal/external marker tracking systems, especially in particle therapy, has not yet been sufficiently tested. In this article, the process of installing an in-house hybrid internal/external motion-tracking system is described and the accuracy level of tracking system was acquired. Our results demonstrated that the developed in-house external/internal combined tracking system has submillimeter accuracy, and can be clinically used as a particle therapy system as well as a simulation system for moving tumor treatment.